(untitled) (Research, Society and Development, 2022)
Contraception in Brazil has millenary origins and provides the human right of the individual to determine the number of children and the interval between them. This study aims to analyze the knowledge of medical course interns about the choice and use of contraceptive methods for primary care patients. This is a descriptive, cross-sectional study with a quantitative approach via an online form available on the Google Forms® platform. When correlating the period of students and the number of correct answers in the questions, it was observed that, among the 40 students of the 9th period, 31 students (21.7%) had an unsatisfactory result, while 9 students (6.3%) obtained satisfactory result 143 questionnaires were selected to compose the present research, being 40 students (9th period), 39 students (10th period), 42 students (11th period) and 22 students (12th period) and when correlating the period of students and the number of correct answers in the questions about knowledge about contraceptive methods, it was observed that, among the 40 students in the 9th period, 31 students (21.7%) had an unsatisfactory result, while 9 students (6.3%) had a satisfactory result, in that context among the 39 students enrolled in the 10th period, 23 students (16.1%) had unsatisfactory results and 16 students (11.2%) had satisfactory results. This study provides valuable insight into the knowledge, awareness, and perception of contraception among medical students.